Analyzing Laser Speckle Pattern Using the Discrete Cosine Transform - Abdul-Ameer, Inbethaq Mohammed Ali (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The use of Cosine transform to analyze the model-noise pattern alteration with different vibration model applied on multimode fiber optics are studied. It’s results compared with the Fourier transform to perform the same analysis using total frequency difference and the computation time, which almost coincide for the both transforms. A discussion for the results and recommendation are introduced.